La musique comme poétique de l’espace et du temps : une exploration à la lumière de Gaston Bachelard - Durand, Maria-Ying (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
In the contemporary context, music, with its acoustic waves, moments of silence, and auditory landscapes, serves as a unique mirror reflecting Gaston Bachelard’s philosophical concepts of spatial intimacy and the dialectics of time. This study delves into the intersection of music and Bachelardian philosophy, exploring how music encapsulates and expresses these profound ideas. We embark on an intellectual journey to investigate whether contemporary musical movements such as spectral music, minimal music or ambient can be analyzed through the lens of Gaston Bachelard’s philosophy. This inquiry leads us to question how music, with its multifaceted dimensions, embodies and transmits the intricate interplay of space and time, as delineated by Bachelard’s philosophical framework.